The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.neuron.2011.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Neural Activities in V1 Create a Bottom-Up Saliency Map

Abstract: The bottom-up contribution to the allocation of exogenous attention is a saliency map, whose neural substrate is hard to identify because of possible contamination by top-down signals. We obviated this possibility using stimuli that observers could not perceive, but that nevertheless, through orientation contrast between foreground and background regions, attracted attention to improve a localized visual discrimination. When orientation contrast increased, so did the degree of attraction, and two physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
174
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(191 citation statements)
references
References 61 publications
13
174
0
Order By: Relevance
“…1A, yellow), which is thought to be the core determinant of attention and gaze (4,5). To date, most studies have reported evidence of saliency and/or priority maps in a distributed network of cortical brain areas [e.g., primary visual cortex (V1) (6)(7)(8)(9), visual area 4 (V4) (10), lateral intraparietal area (LIP) (11)(12)(13), and frontal eye fields (14,15)]. However, there is mounting evidence for a subcortical saliency mechanism in the premammalian optic tectum (16)(17)(18) or superior colliculus (SC) in primates (Fig.…”
mentioning
confidence: 99%
“…1A, yellow), which is thought to be the core determinant of attention and gaze (4,5). To date, most studies have reported evidence of saliency and/or priority maps in a distributed network of cortical brain areas [e.g., primary visual cortex (V1) (6)(7)(8)(9), visual area 4 (V4) (10), lateral intraparietal area (LIP) (11)(12)(13), and frontal eye fields (14,15)]. However, there is mounting evidence for a subcortical saliency mechanism in the premammalian optic tectum (16)(17)(18) or superior colliculus (SC) in primates (Fig.…”
mentioning
confidence: 99%
“…However, attentional phenomena discovered in the lab do not always extend to real-world tasks. For example, Hayhoe and colleagues showed that whereas perceptual saliency is a major factor driving attention in laboratory tasks (Itti & Koch, 2001;Li, 2002;Theeuwes, 1994;Zhang, Zhaoping, Zhou, & Fang, 2012), it has virtually no impact on realistic tasks (Foulsham et al, 2014; for a review, see Tatler, Hayhoe, Land, & Ballard, 2011). In addition, the spatial reference frame used to code attended locations is more flexible in an outdoor search task than on a computer (Jiang & Won, 2015;Jiang, Won, Swallow, & Mussack, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The dominant view that a saliency map is generated in the parietal cortex has been challenged because a bottomup saliency map is created in V1 [1] . Likely, an increase in brain magnesium enhances both short-term synaptic facilitation and long-term potentiation and improves learning and memory functions [3][4][5] . Moreover, long non-coding…”
Section: Neural Circuit Research In Emotion and Memorymentioning
confidence: 99%